Characterization of algae residue biochar and its application in methyl orange wastewater treatment - Zhu, Hao (Water science and technology : a journal of the International Association on Water Pollution Research, 2021)
In this work, Spirulina residue was used as the raw material to prepare different biochars by changing the pyrolysis time. Moreover, the obtained products were characterized by scanning electron microscopy, transmission electron microscopy, Raman spectroscopy, Fourier transform infrared spectroscopy, and X-ray diffraction energy spectra. This experiment used the batch adsorption method to study the adsorption effect of pH, dosage, and pyrolysis time on methyl orange. The adsorption of methyl orange onto Spirulina residue biochar (SRBC) were fitted with the Langmuir isotherm model and pseudo-second-order kinetics. The results showed that the surface functional groups of SRBC obtained by dry pyrolysis were abundant, and could effectively adsorb methyl orange dye in an aqueous solution. The sample prepared at 500 °C for 5 h had the best adsorption effect on methyl orange. The change of pyrolysis time will affect the physicochemical properties of biochar from Spirulina residue, thereby affecting its adsorption effect on methyl orange dye. The analysis showed that the chemical adsorption of SRBC on methyl orange might be the primary way of dye removal. The results can provide a reference for preparing biochar from algae residue and biochar application in the removal of dye wastewater